The Impact of Policy Orientation on Green Innovative Performance: The Role of Green Innovative Capacity and Absorptive Capacity - Li, Bin; Lei, Yongxin; Hu, Minqi; Li, Wenjing (Frontiers in Environmental Science, 2022)
Rapid economic development is accompanied by serious problems such as serious environmental pollution, and a lack of innovation, which has led managers to place greater emphasis on green innovation as a way to alleviate the pressure that companies are putting on the environment. Based on Porter's hypothesis and absorptive capacity perspective, this study explores the impact of policy orientation on firms' green innovative performance, and further explores the moderating effect of absorptive capacity on policy orientation and green innovative capacity. As a result, we identify that (1) policy orientation has a significant positive effect on a green innovative capacity. (2) green innovative capacity plays a mediating role between policy orientation and green innovative performance; (3) absorptive capacity plays a moderating role between policy orientation and green innovative performance. Our findings theoretically enrich the literature on Porter's hypothesis and absorptive capacity perspectives and provide a reference for green innovation practices.